THE ROLE OF PERCEPTIVE ABILITY IN THE TRAINING OF PERSONNEL AT THE LEVEL OF ERUDITION (Universal International Scientific Journal, 2026)
This thesis analyzes the priority areas of training competitive personnel at the level of erudition in the modern education system and the role of perceptual abilities in this process. In the course of this research, the essence of the concept of erudition, its components, and the importance of perceptual sensitivity in pedagogical activity in cognitive processing of information and establishing effective communication with students were studied. Also, scientific conclusions were made on the pedagogical possibilities and methods of developing perceptual abilities.
Keywords: Erudition, perceptive ability, competence, qualified personnel, pedagogical sensitivity, cognitive integration.